Retroduodenal perforation as complication of endoscopic interventions in obstructive jaundice - M. P. Korolyov; L. E. Fedotov; R. G. Avanesyan; A. L. Ogloblin; B. L. Fedotov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The research demonstrated possibilities of low invasive methods in treatment of retroduodenal perforations in patients with choledolithiasis complicated by obstructive jaundice. MATERIAL AND METHODS. Methods of treatment management were described in patients with retroduodenal perforation after endoscopic papillosphicterotomy and lithoextraction. RESULTS. The low invasive methods, which were described in this article, allowed doctors to cope with retroduodenal perforation without open surgical interventions. CONCLUSIONS. The choice of management strategy of patients with retroduodenal perforation depended on the time period, when it was revealed. Combined endoscopic and percutaneous methods could be successfully applied in treatment management of patients with retroduodenal perforation.